Tubular graphitization furnace - ZHAO JINGCHEN (2014)
The utility model discloses a tubular graphitization furnace which is characterized by comprising a furnace body, wherein the lower end of the furnace body is fixedly connected with a cooling device; the lower end of the cooling device is fixedly connected with a cooling water jacket; a graphite pipe vertically and sequentially passes through the furnace body, the cooling device and the cooling water jacket; an inlet end of the graphite pipe is fixedly connected with a feeding funnel; a first valve and a second valve are arranged on the graphite pipe positioned at the lower end of the feeding funnel; an oxygen removal device is arranged on the graphite pipe positioned between the first valve and the second valve; the outlet end of the graphite pipe is fixedly connected with a relief device; a third valve is arranged on the graphite pipe positioned at the upper end of the relief device; a fourth valve is arranged on the graphite pipe positioned at the lower end of the relief device; a vacuum pipeline and a nitrogen pipeline communicated with the furnace body are arranged on the lower part of the furnace body; a chlorine pipeline communicated with the graphite pipe is arranged on the lower part of the furnace body. The tubular graphitization furnace is simple and applicable structure, continuous in production, low in power consumption, energy-saving, environmentally friendly, high in capacity and high in stability and is particularly suitable for high-temperature treatment of lithium ion battery anode materials.